Digestibilidade do capim-elefante (Pennisetum purpureum Schum): correlação "in vivo" X "in vitro" - Farias , Iderval; Joaquim Ferreira , José; Gomide, José Alberto (Revista Ceres, 2025)
Elephant-grass silage samples of known apparent dry-matter digestibility were fermented over 24 h with rumen fluid for the determination of the in vitro dry-matter digestibilities. Regression and correlation analyses between the "in vivo" (Y) and "in vitro" (X) figures allowed the establishment of the regression equation y = 14,83 + 0,86 X and the correlation coeficient r = + 0,97. The standard error of estimate (Sy.x) was + 2.17, whereby it was concluded to be possible to estimate the apparent dry matter digestibilityof elephant grass from the "in vitro" values.